Filem Mikrosfera Akrilik Terpegun Alizarin Merah S Untuk Pengesanan Pendarfluor Optik Asid Borik - Raja Zaidatul Akhmar Raja Jamaluddin; Musa Ahmad; Lee Yook Heng; Ling Ling Tan (Penerbit UKM, 2024)
Indexed by WOS/Scopus/ERA/MyCite